Implementation of Honesty Canteen Program as Character Education Strategy in Elementary Schools - Hidayat, Ujang Syarip (Baileo: Jurnal Sosial Humaniora, 2024)
This study aims to examine the implementation of the honesty canteen program as a strategic approach to character education in elementary schools, with a focus on developing students’ integrity—particularly the value of honesty. Conducted at State Elementary School 10 Regol Garut, this research employs a qualitative case study method, utilizing observations and in-depth interviews as primary data collection techniques. Data analysis follows the Miles and Huberman model, encompassing data condensation, display, and conclusion drawing. The findings reveal that the honesty canteen serves not only as a place for transactions but also as a medium for experiential learning that reinforces honest behavior through four key components: routine, spontaneous, exemplary, and conditioning activities. The implementation involves self-service and active student participation, encouraging students to practice honesty in everyday situations. Despite its effectiveness, challenges such as students’ inconsistent behavior, income disparities, and operational limitations persist. The novelty of this study lies in its detailed contextual analysis of the honesty canteen as a practical, low-cost character-building tool embedded in daily school life. This research contributes to the field of social sciences and humanities by offering a replicable model of value-based education that fosters integrity through direct experience and community reinforcement. It recommends sustained support from schools and broader social environments to ensure long-term character development in students.